CONCEPTUALISING THE SERVICE EXCELLENCE AND ITS ANTECEDENTS: THE DEVELOPMENT OF STRUCTURAL EQUATION MODEL - Yuhanis Abdul Aziz; Khairil Wahidin Awang (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
Increasing and maintaining service excellence in the tourism and hospitality industry are known to enhance the customers’ satisfaction which could bring more profits to the organizations. This paper focuses on the antecedents of service excellence, in particular the relationship with service characteristics, empowerment of employees, service excellence, and its impact on the selected outcomes. Using the existing literature, a proposed structural equation model with its associated hypotheses is developed to explain the relationship between service experience antecedents and its associated outcomes. Hence, the proposed model provides understanding on the inter-linkages among service excellence, its antecedents and the outcomes. It provides some clearer insights into the importance of managing customer service experience which can contribute to customer satisfaction as well as enhancing organization competitive advantage. Thus the empirical work is required to test various research propositions empirically. The Implications for the practitioners are also discussed.